2019
DOI: 10.5897/ajb2018.16446
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assessment of yams (Dioscorea spp.) from Ethiopia using inter simple sequence repeat (ISSR) markers

Abstract: The genetic diversity and relationships of 70 accessions of yam belonging to Dioscorea cayenensis/Dioscorea rotundata complex (55), Dioscorea bulbifera (13) and Dioscorea alata (2, as a reference) were assessed using six inter simple sequence repeat (ISSR) primers. DNA was extracted from a bulk of two plants per accession using a modified cetyl trimethyl ammonium bromide (CTAB) method. Six ISSR primers amplified 77 fragments with 75 (97.40%) polymorphism at genus level. The genetic diversity, estimated by gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Our results agree with Ousmael et al (2019), who assessed the genetic diversity of 77 accessions of Dioscorea spp. using six ISSR primers, finding high genetic diversity at the genus level with Shannon index of 0.36 and 0.53, respectively.…”
Section: Genetic Diversitysupporting
confidence: 93%
See 3 more Smart Citations
“…Our results agree with Ousmael et al (2019), who assessed the genetic diversity of 77 accessions of Dioscorea spp. using six ISSR primers, finding high genetic diversity at the genus level with Shannon index of 0.36 and 0.53, respectively.…”
Section: Genetic Diversitysupporting
confidence: 93%
“…Moreover, Loko et al (2016) found 96% variation within populations and only 4% among populations using 41 microsatellite markers to study the genetic diversity and relationships between 64 local varieties of yam. The high variation within populations could be due mainly to evolutionary dynamics and/or admixture in the field possibly facilitated by pollen flow (Ousmael et al, 2019). Our results demonstrate that the genetic diversity of a yam germplasm bank can be efficiently enriched when wild type genotypes are collected in one region and a low number of rare or diverse genotypes from other regions are later incorporated.…”
Section: Bayesian Analysis Of Population Structurementioning
confidence: 77%
See 2 more Smart Citations
“…The genetic variation in this study was also explained using AMOVA analysis that partitioned total variation within the population rather than among population indicating close evolutional relationships and admixture among yam genotypes, especially those that were sourced from Ghana and Nigeria. Similar results were reported by Kedra et al [ 58 ] in yams from Ethiopia, Loko et al [ 59 ] in guinea yams from Benin, Muluneh et al [ 60 ] in yams from Ethiopia, and Wendawek et al [ 61 ] in cultivated and wild yams in Ethiopia wherein within-population variation were higher than among population.…”
Section: Discussionsupporting
confidence: 86%